A systematic review on leaching of rare earth metals from primary and secondary sources - Shahbaz, Aiman (Minerals engineering, 2022)
•Screening of various lixiviant has been discussed in detail for the extraction of REM from primary and secondary sources.•The separation process for REM extraction from aqueous solution by using extractants such as TBP, Cyanex 272, D2EPHA, and PC 88A has been reviewed.•Bioleaching of REM by using different biosorbent has been discussed.•The role of ionic liquids in the extraction of REM and solvent extraction technique is also highlighted. Rare earth metals (REM) have applications in multitudinous fields such as the medicinal industry, nuclear technology, and agricultural implementations. Recently, this has caused considerable interest within the community due to its growing demand which leads scientists to explore effective, economical, and safer ways of extraction from primary and secondary sources. This review is of pivotal importance as it summarizes the requirements of REM worldwide, leaching of REM from ores, recycling of REM from scrap materials, end-life-products, and industrial wastes. This represents an important topic to explore as it demonstrates existing REM production and effective recovery pathways, and highlights the critical challenges such as the harsh harmful leaching technologies used to recover REM from primary and secondary sources. A comprehensive classification of REM, hydrometallurgical extraction, bioleaching, separation techniques, and sustainable approaches to supporting a circular economy has been extensively discussed. This factual and comprehensive overview of past, present and future aspects of REM recovery technologies will be helpful to researchers in developing efficient leaching pathways for REM recovery.